Epidemiologic profile of breast cancer in Iran: A systematic review and meta-analysis - Zohreh Sanaat; Roya Dolatkhah (Elsevier, 2024)
Background: In Iran, the latest reports from different regions indicate that incidence and mortality rates of breast cancer have significantly increased. Methods: All manuscripts were screened for eligibility according to inclusion criteria. Epidemiological, analytical, cross-sectional, descriptive, and population-based studies were recruited. Results: Pooled estimated results were ASIR = 32.10, CIR = 28.99, and APC = 7.54%. However, the results indicated an increasing trend of all incidence indexes including ASIR, CIR, and APCs. Conclusion: This is noteworthy that there has been a rapid increase in the incidence of breast cancer. The estimated results were in accordance with the last reported results of Iran.